Strategi Memenangkan Pitching Pada Social Media Marketing - Satria Rangga Pamungkas; Duddy Zein; Teddy Kurnia Wirakusumah (Institut Nalanda, 2024)
This research aims to find out the strategy for winning the Plaza Senayan social media marketing pitch by Clay Creative House. This research uses a qualitative method with a descriptive study approach and data collection is carried out through in-depth interviews and documentation. The research results show that in responding to the social media marketing brief provided by Plaza Senayan, Clay Creative House went through previous research stages to ensure that Clay Creative House had prepared itself with sufficient background information to better understand the client's needs. Apart from that, in preparing the process of working on Plaza Senayan's social media marketing pitch deck, Clay Creative House organized it by carefully analyzing the social media marketing brief provided by Plaza Senayan to then translate it into specific tasks and job descriptions. As for carrying out the idea filtering process while working on Plaza Senayan's social media marketing pitch deck, Clay Creative House filters the ideas that have been raised by implementing a combination of control and creativity carried out by the project manager. There are several activities carried out by Clay Creative House during the process of working on Plaza Senayan's social media marketing pitch deck which are categorized into a creative process which includes initiation, knowledge distribution, polyphony, imagination, idea formulation, and consolidation. The structure of content preparation in the pitch deck proposal presentation slides is also prepared based on the AIDA approach where the introductory part of the proposal uses a persuasive approach through narrative storytelling to get attention, then uses data descriptions and strategy visualization to attract interest, after that a presentation of strategy implementation and content mockups to build a sense urgency, needs and desires of the client, and finally the implementation of the slogan in the closing as a form of CTA to encourage action (conversion). Meanwhile, in direct presentations to clients, Clay Creative House implements aspects of mutual attentiveness, positivity and coordination which enable them to implement adjustments to the character and interaction style of the interlocutor, namely Plaza Senayan.